ANTIOXIDANT ACTIVITES AND PHYTOCHEMICAL ANALYSIS OF METHANOL EXTRACT OF LEAVES OF HYGROPHILA AURICULATA (SCHUMACH) HEINE - Raaman, N. (International Journal of Current Pharmaceutical Research, 2015)
Objective: The aim of the present investigation was to evaluate the phytochemical constituents, and antioxidant properties of the methanol extract of leaves of Hygrophila auriculata. Methods: The phytochemicals in the methanol extract of leaves of H. auriculata were determined qualitatively and quantitatively using standard methods. The antioxidant activities were carried out by DPPH free radical scavenging assay, ABTS∙+radical cation scavenging assay OH• radical scavenging assay, NO•radical scavenging assay, Fe2+chelation assay, Fe3+reducing power assay and phosphomolybdenum reduction assay methods. Results: The methanol extract of leaves of H. auriculata revealed good radical scavenging activities and reducing power activities which were found to increase with the increasing concentration of the extract. The presence of phenols and flavonoids in the methanol extract of leaves of H. auriculata were 342.64 mg/g and 124.4 mg/g, respectively. Conclusion: The present study revealed that the methanol extract of leaves of H. auriculata showed significant antioxidant activities.